Adolescente autor de ato infracional: falência do pai ou falência da pátria? - Mattos, Luciana (2008)
The present research paper aims to carry out an analysis based on reports, accounts and assessments structured by psychologists and Judicial Power social workers, focusing on issues related to family dynamics, markedly expressions such as disorganized family , father frailty and others alike, present in the aforementioned documents, dialoging with the social issue. This research has emerged from the work I developed, as a psychologist, at the then FEBEM/SP São Paulo s State Foundation for The Well-Being of Minors and at AMAR Association of Mothers and Friends of Children and Adolescents at Risk , opportunity in which I had access to various reports by adolescents, as well as the chance to get in contact with their parents. Concerning the latter, a tendency towards excessive blaming has been observed, especially with regard to both the presumed failures by the father in the exercise of his role, and, on the other hand, the low relevance attributed to other life instances of the adolescent, evidenced by the absence of data on socio-economic factors. The sample, obtained with the authorization of DEIJ (São Paulo s Department of Enforcement of Childhood and Youth), comprised twenty-nine lawsuit cases related to adolescents who had committed transgressions and were serving socioinstructional penalties of the internment type. The methodology applied was that of content analysis, by L. Bardin, and thereby material analysis categories were determined. As for the result, in the majority of social studies, no reference to social issues was observed, highlighting a silence with regard to the State s lack of commitment to formulating and executing public care policies. The so-called problems are reduced to family and personality issues, with depoliticized observations, erased of their violent historical conditions